MULTIPLE DISCRIMINATION IN THE HEALTH CARE: THE CASE OF WOMEN WITH DISABILITIES - ŠUMSKIENĖ, Eglė; JONUTYTĖ, Jurga; AUGUTIENĖ, Rita; KARALIŪNIENĖ, Rūta (Socialinė teorija, empirija, politika ir praktika, 2015)
The aim of this article is to identify experiences of women with disabilities in the health care sector, while drawing special attention to the manifestations of multiple discrimination. The biomedical approach dominates in the system of health care. Health care professionals stress the deficiency of women with disabilities, moreover, disability is perceived as the main determinant of their personalities. Reproductive health is the particular sphere where both identities meet – disability and gender. The multiple discrimination experienced in this sphere is particularly intense. Women with disabilities stress their female identity, care for their reproductive health and desire to become mothers. Nevertheless, they confront strong opposition by health professionals who first and foremost perceive them as persons with disabilities, incapable of and unrecommended to procreate.
Keywords: women with disabilities; health care sector; multiple discrimination